1991
DOI: 10.1002/jsfa.2740570207
|View full text |Cite
|
Sign up to set email alerts
|

Eating quality and growth of rainbow trout (Oncorhynchus mykiss) on feed with different admixtures of leaf nutrient concentrate

Abstract: The eflects, with regard to eating quality and to growth, of leaf nutrient concentrate (LNC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…1997 ). However, the results of the present study, together with the findings of others ( Johansson et al . 1991 , 1995; Bjerkeng et al .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…1997 ). However, the results of the present study, together with the findings of others ( Johansson et al . 1991 , 1995; Bjerkeng et al .…”
Section: Discussionsupporting
confidence: 76%
“…It might be speculated that larger deviations in proximate composition could result in more profound differences in taste experience among panellists; but further studies in this important area are required. It has been suggested that lipid increases flesh juiciness in rainbow trout ( Johansson et al . 1991 ) sea bream Sparus aurata ( Orban et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fast growth also masked the acidulous taste associated with freshness (Johansson et al . ). However, limited information is available about the effect of growth rate under restricted feeding on quality of fish grown to the same size (Rasmussen & Ostenfeld ).…”
Section: Introductionmentioning
confidence: 97%
“…For example, Folkestad et al (2008) indicated that fast growth during 2 months prior to harvest was significant importance for flesh softening in both raw and smoked salmon fillets, whereas fast growth led to the fish flesh a less firm texture and a less favourable fatty acid (FA) pattern (Johansson et al 1995). Moreover, fast growth also masked the acidulous taste associated with freshness (Johansson et al 1991). However, limited information is available about the effect of growth rate under restricted feeding on quality of fish grown to the same size (Rasmussen & Ostenfeld 2000).…”
mentioning
confidence: 99%
“…Salmonids, especially Atlantic salmon (Salmo salar) , on the Danish market are mostly farmed fish. Several studies show how the sensory properties of salmonids are influenced by different farming conditions, e.g., feed composition (Johansson et al . 1991; Regost et al .…”
Section: Introductionmentioning
confidence: 99%